Micro‐Coil Neuromodulation at Single‐Cell and Circuit Levels for Inhibiting Natural Neuroactivity, Neutralizing Electric Neural Excitation, and Suppressing Seizures - Kayeon Kim; Xiyuan Liu; Bingdong Chang; Guanghui Li; Gwendoline A. E. Anand; Su Genelioglu; Alexandra Katherine Isis Yonza; Andrew J Whalen; Rune W Berg; Shelley I Fried; Anpan Han; Changsi Cai (Advanced Science)
Abstract Micromagnetic stimulation (µMS) emerges as a complementary method for neuromodulation. Despite major advances in neural interface technology, there are limited options for neural inhibition. Here, a microchip‐based implantable micro‐coil device is presented to achieve high spatial precision for cortical inhibition. Cortical in vivo two‐photon imaging of spontaneous neural activity showed µMS reversibly suppressed single cells, and as µMS magnitude is increased, the suppressed cell population increased from 14% to 41%. At the circuit level, the average suppressed area is 0.05 mm2, seven times smaller than the activated area induced by micro‐electrode stimulation (µES). It is discovered that neurons responded more strongly to µMS than to µES, which is exploited to effectively neutralize the neural excitation induced by concurrently delivered strong µES (80 µA). Moreover, µMS mitigates hyperactive neural firing caused by pharmacologically induced seizures, reducing seizure amplitude by 54%. These findings underscore the potential of µMS as a precise, effective, and versatile tool for localized neuromodulation with an effect of opposite polarity from µES. Complementing optogenetic and electrical stimulation for multi‐functional neural interfaces, µMS holds promise as a unique neuroscience research tool and as a potential therapeutic intervention method for precisely suppressing hyperactive brain circuits.